Prevention of Cyberbullying Against Children from the Aspect of Criminology - Abdillah, Ahmad Yusron; Madjid, Abdul; Ruslijanto, Patricia Audrey (International Journal of Business, Law, and Education, 2024)
Bullying is happening all around us, even in schools and colleges. schools and colleges. Cases of cyberbullying in Indonesia are very high. Criminology can also be referred to as the sociology of criminals as this field is concerned with human with human learning that goes against social norms. Legal regulation of cyberbullying criminal offense of cyberbullying in Indonesia contained in the Criminal Code and outside the Criminal Code, namely Undang-Undang No.11 Tahun 2008 About Electronic Information and Transactions which has been updated with Undang-Undang No. 1 Tahun 2024. The cause of children committing cyberbullying is the influence of the child's socialization that normalizes the act, prevention strategies for cyberbullying.normalizing these actions, the appropriate prevention strategy is to supervise children's socialization and provide understanding that cyberbullying is a bad act and can be charged with criminal sanctions. and can be charged with criminal sanctions.